Ambiguitas Politik Agama dalam Demokrasi - A. Bakir Ihsan (Refleksi: Jurnal Kajian Agama dan Filsafat, 2008)
Islamic political parties in Indonesia face two dilemmas: structural and cultural. Structurally, Islamic principles are not compatible with the state ideology, which positions religion as a social entity rather than a formal reference for the state. Culturally, Islamic political parties do not exhibit the distinctiveness of their principles in aggregating and articulating the aspirations of society. There is even a tendency to extend their roles as an effort to gain support without being bound to their principles. Given this situation, what is the significance of principles for political parties? In the context of Islamic principles, what can be expected from the existence and function of Islamic political parties in the national political constellation?